Childbirth...between the hammer of superstition and the anvil of cultureA study in population anthropology - Hadeel Toman Muhammad, Asst. Prof. Dr.; Firas Abbas Fadhel Al-Bayati, Prof. Dr. (lark, 2025)
Abstract: Childbirth has become a source of concern for many wives, especially within families governed by social constraints rooted in traditions and customs that differ from one family to another. This issue is further compounded in societies where traditional cultures and social norms dominate perceptions of fertility and the desire for children, particularly when it comes to determining the gender of the child. This study aims to uncover prevailing societal traditions related to reproduction and gender preference. The researchers employed both analytical and historical methodologies to examine these practices, and their findings reveal the following key points: • Childbirth is considered one of the most vital biological and social processes and is regarded as sacred across all societies. It also represents one of the most important goals of marriage. • Couples, especially in traditional societies like ours, often face negative social pressure and criticism if they experience delays in having children. These pressures can affect their psychological and social well-being, and even threaten family cohesion, compelling them to resort to questionable practices. • Despite advancements in science, medicine, and cultural awareness, many of these superstitious or traditional reproductive practices still persist in our society. This reflects an ongoing level of social acceptance of such behaviors.